2017
DOI: 10.1039/c7cp00978j
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of ionic liquids and surfaces of graphene related nanoparticles under high pressures

Abstract: High-pressure infrared spectroscopy was used to study the interactions between 1-methyl-3-propylimidazolium iodide [MPIM]I and graphene-based nanoparticles. The results obtained at ambient pressure indicate the imidazolium ring of the cation to be a more favorable moiety for adsorption than alkyl C-H groups at ambient pressure. Upon increasing the pressure, the dominant C-H band of pure [MPIM]I yields a significant red frequency shift. As the mixtures, i.e., graphene oxide (GO)/[MPIM]I, reduced graphene oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Therefore, IR methodologies may be useful to probe the structures of ionic liquids at solid surfaces. Furthermore, it can be seen from some studies that there are weak hydrogen bonds between the aromatic C–H in the cations and the anions [36,37,38,39,40]. Moreover, the contribution to charge-assisted hydrogen bond energy by coulombic interactions is especially significant and the C–H…O hydrogen bonding in 1,3-dimethylimidazolium methyl sulfate is one of the dominating interactions [32].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, IR methodologies may be useful to probe the structures of ionic liquids at solid surfaces. Furthermore, it can be seen from some studies that there are weak hydrogen bonds between the aromatic C–H in the cations and the anions [36,37,38,39,40]. Moreover, the contribution to charge-assisted hydrogen bond energy by coulombic interactions is especially significant and the C–H…O hydrogen bonding in 1,3-dimethylimidazolium methyl sulfate is one of the dominating interactions [32].…”
Section: Introductionmentioning
confidence: 99%
“…The application of high pressure is an excellent technique to investigate the ordering of ILs on a solid surface [20,21,22]. The changes in the spectral characteristics induced by high pressures are of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…The local structures of ILs appear disturbed under high pressure, and pressure-enhanced interfacial interactions may occur between the ILs and the solid surfaces, under high pressures. The various degrees of associations between the ILs and the solid surfaces at high pressures may arise from a reorganization of local structures and the hydrogen bonding network [20,21,22,23]. Upon compression, the relative weights of the intermolecular forces defining the aggregation states and the intramolecular interactions (molecular bonding) are changed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of pressure as a variable allows one to separate the thermal and volume effects. Studies have shown the potential significance that pressure has on controlling the strength of intermolecular hydrogen bonding, especially the relatively weak C-H-X hydrogen bonds, where X is an anion atom [15][16][17][18]. Pressure-dependent changes in spectral features indicate that nanoparticles tend to influence local structures of certain ILs under high pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure-dependent changes in spectral features indicate that nanoparticles tend to influence local structures of certain ILs under high pressures. As certain ILs have been employed as graphene stabilizers, previous studies suggest that imidazolium ILs with short alkyl chain lengths (n < 4) may be suitable choices to modulate the performance of energy storage devices via pressure-enhanced interfacial interactions [15]. In order to obtain detailed insights into the ionic liquid/Al 2 O 3 interactions, we use variable pressure as a window into the nature of hydrogen bonding structures of imidazolium ionic liquid/Al 2 O 3 mixtures in this article.…”
Section: Introductionmentioning
confidence: 99%